EL MOVIMIENTO NEORURAL FRENTE AL DESPOBLAMIENTO RURAL DE LA PROVINCIA DE BURGOS: PROMOCIÓN DE LA PRODUCCIÓN Y CONSUMO LOCAL, LA SOSTENIBILIDAD Y LA SIMPLICIDAD VOLUNTARIA - Alonso, Javier Miguel (2020)
The following essay collects the activities developed by the trainee during the internship period in Ábrego Association, within the theorical context of rural depopulation in the province of Burgos, phenomena that is increasing in the Spanish countryside. The position of the association inside of the movement for rural development and “neorruralism” will be observed, as well as its influence in the region. Theory of rural society in modern times and its relationship with the “neorrural movement” will be studied. A detailed exposition of all the work realised during the internship is made, explaining the trainee implication in activities and events developed by Ábrego.